Elevating the charge separation of MgFe2O4 nanostructures by Zn ions for enhanced photocatalytic and photoelectrochemical water splitting. (November 2021) - Kumar, G.Mohan; Cho, H.D.; Lee, D.J.; Kumar, J.Ram; Siva, C.; Ilanchezhiyan, P.; Kim, D.Y.; Kang, T.W.
Abstract: Magnesium ferrites (MgFe2 O4 ) are important class of ferrites that have been receiving greater attention as promising excellent photocatalyst due to its low cost, wide light spectrum response and environment-friendly nature. However, its poor electronic conductivity and fast charge carrier recombination hinders its electrocatalytical applications. Hence, accelerating charge carriers separation efficiency is important to modify the photoelectrochemical performance of MgFe2 O4 . Herein, novel Zn ions doped MgFe2 O4 nanospheres are fabricated for the first time. Zn ions are doped into MgFe2 O4 nanostructures from surface to enhance their charge separation efficiency. The doped MgFe2 O4 nanostructures show significant photocatalytic activity and enhanced photocurrent density than that of pristine MgFe2 O4 .The improved photoelectrocatalytic performance is attributed to doping effect, were Zn ions actually enhance the conductivity. Zn ions enhance the activity of MgFe2 O4 and accelerate the charge transfer properties in MgFe2 O4 . The results highlight that Zn doped MgFe2 O4 nanospheres could be a potential candidate for photocatalytic and photoelectrochemical applications. Highlights: Zn doped MgFe2 O4 nanospheres was synthesized via simple hydrothermal method. A three fold higher photocurrent density was observed in water splitting. A two fold improvement in photocatalytic rate constants was noted in Zn doped MgFe2 O4 nanospheres. The degradation of organic dye was mainly via OH radicals in oxidation mechanism.